Biometric characteristic of the hard palate changes in children with dysplasia of the connective tissue (LLC "Endo Press", 2020)
The research objective was definition of biometric changes of the hard palate in children with various intensity of dysplasia of the connective tissue (DCT). Studying of the height of crest of the hard palate in children aged from 10 to 14 years was carried out. Features of anatomical changes of crest of the hard palate and narrowing of the upper dentition depending on DCT intensity which characterize that the more DCT intensity, the higher height and narrowing of dentition have been determined. These research data can be used in dentistry by drawing up a complex plan of treatment-and-prophylactic and rehabilitation among children with DCT.